RANCANG BANGUN APLIKASI PENGENDALIAN INVENTORI OBAT PADA KLINIK DRYN SURABAYA - Luhulima, Edyson; Setyawan, Henry Bambang; Rahmawati, Endra (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Abstract: Dryn clinic is a clinic that consistently apply the concept of healthy living by combining elements of beauty and health of the skin and body. The business process is currently part pharmacist can not determine how much product will be purchased to the supplier. The types of drugs that exist today reaches more than 300 (three hundred) and the current system has not been able to determine how the most optimal amount of inventory. Consequently Dryn clinic will experience shortages or excess stock due to the absence of a process of inventory control for optimal reservation. The impact is the customer had to wait until the product is available. When the clinic Dryn have excess stock, the impact is Dryn must add the cost of product storage.Based on the above problems, inventory control applications made using the Reorder Point (ROP) determining when a product should be done reordering and methods Ecomomic Order Quantity (EOQ) to get the optimal amount of ordering a product.With the application of the drug inventory control Dryn Clinical information can be obtained form the optimal number of products in the booking in the next period and a reordering that is used to control the supply of products so there is no shortage of stock.Keywords: Sales, Inventory Control, and Purchase.